2015
DOI: 10.3109/13880209.2014.959612
|View full text |Cite
|
Sign up to set email alerts
|

Nerium indicumleaf alleviates iron-induced oxidative stress and hepatic injury in mice

Abstract: Context: Nerium indicum Mill. (Apocynaceae) was reported for its efficient in vitro antioxidant and iron-chelating properties.Objective: This study demonstrates the effect of 70% methanol extract of N. indicum leaf (NIME) towards in vitro DNA protection and ameliorating iron-overload-induced liver damage in mice. Materials and methods: Phytochemical and HPLC analyses were carried out to standardize the extract and the effect of Fe 2+ -mediated pUC18 DNA cessation was studied. Thirty-six Swiss Albino mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…Our previous study showed potent iron chelation ability by the oleander extracts [11]. Recent studies also showed that 70 % hydro-methanolic extract of N. indicum leaf could ameliorate hemochromatosis and fibrosis in liver due to its potent antioxidant and iron chelation activities [13, 14]. Thus, the present study corroborates the previous findings of the antioxidative protection by oleander extracts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our previous study showed potent iron chelation ability by the oleander extracts [11]. Recent studies also showed that 70 % hydro-methanolic extract of N. indicum leaf could ameliorate hemochromatosis and fibrosis in liver due to its potent antioxidant and iron chelation activities [13, 14]. Thus, the present study corroborates the previous findings of the antioxidative protection by oleander extracts.…”
Section: Discussionsupporting
confidence: 91%
“…The extracts also demonstrated free radical scavenging activities against various reactive species associated with hepatotoxicity such as hydroxyl (OH ● ), superoxide (O 2 ●− ), peroxynitrite (ONOO − ), singlet oxygen ( 1 O 2 ), hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO), in addition to potent iron (Fe 2+ ) chelation activities, overload of which may lead to haemochromatic liver [12]. It is interesting to note that, a recent in vivo preliminary study demonstrated that N. indicum leaf extract ameliorates haemochromatic conditions in mouse [13]. Moreover, another recent study showed that N. indicum leaf extract attenuates CCl 4 mediated hepatotoxicity in Swiss albino mouse [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that both SF and TAU significantly reduced the aggravations in liver damage associated with iron overload. The effect of SF is explained by its antioxidation, which is consistent with previous studies that reported that antioxidant protects against liver damage in iron-overloaded mice models [20,21,22].…”
Section: Discussionsupporting
confidence: 91%
“…One-third of the patients experienced improvement in mT2* and no new arrhythmias were detected during the 24 months (Aydinok et al, 2015). for example, silymarin (Moayedi Esfahani et al, 2015), phytic acid (Bhowmik et al, 2017), and 70% methanol extract of Nerium indicum leaf (NIME) (Ghate, Chaudhuri, Panja, & Mandal, 2015). Some of them showed less potency in terms of chelating iron when compared to several standard iron chelators (NIME vs DFX (Ghate et al, 2015)), and may not be suitable for iron chelation monotherapy.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The release of ferritin iron is essential for chelation. This process is facilitated by reducing agents such as ascorbate (Ghate et al, ). For this reason, some anti‐oxidants may be able to improve the efficacy of iron chelation.…”
Section: Prevention Of Arrhythmia and Af In β‐Thalassemia Patientsmentioning
confidence: 99%